Outlook and Challenges of Nanotechnologies for Food Packaging. Issue 12 (6th June 2016) - Wyser, Yves; Adams, Michael; Avella, Maurizio; Carlander, David; Garcia, Leonor; Pieper, Gabriele; Rennen, Monique; Schuermans, Jeroen; Weiss, Jochen
Abstract : Nanotechnology has been considered to have high potential for food packaging applications very early on. The ability to provide additional consumer benefits through the improvement of key properties of packaging materials and the creation of new functionalities means that the increased use of nanomaterials and nanotechnologies is highly likely. It has however up to now failed to reach the widespread use that was initially expected, mainly because of remaining uncertainties on the safety of these materials during the various stages of their life‐cycle, which limit legal and consumer acceptance. This paper aims at presenting the latest developments in the field of nanotechnologies for food packaging applications, describing the legal framework linked to their usage and attempts to clarify the current knowledge of the safety of these materials both for the consumer and the environment. It is shown that particulate migration into foodstuff is absent in many applications, which drastically reduces the potential risk during the use phase of packaging materials, i.e. the exposure of the consumer to nanoparticles. Other release routes are also evaluated, showing that, although safe in normal use conditions, prudence should still be used, especially with regard to release after disposal of the materials. Copyright © 2016 The Authors Packaging Technology and Science Published by John Wiley & Sons Ltd Abstract : This paper reviews the work in the field of nanomaterials and nanotechnology with a specific focus on food packaging applications and provides clarification regarding the barriers that have hindered their wider use. It explores current technological developments along with potential benefits in terms of property enhancement. The legislative framework is also investigated, along with potential safety risks.